PENGARUH HARGA DIRI TERHADAP KECEMASAN DI RUTAN PEREMPUAN KELAS II A MEDAN - Lusiana Gultom, Putri Three Wednesday; Lumbantoruan, Rachel Mia (JURNAL PSYCHOMUTIARA, 2024)
Anxiety in female inmates occurs because of the fear that they will be treated poorly or considered worthless, unable to accept their situation with the status that is accepted as a correctional inmate and the concern of the inmates of the correctional facility what the future will be after serving the sentence at the Class Women's Rutan. II A Medan. Correctional inmates who are serving a period of time are prone to experiencing anxiety problems that occur due to the inability of the individual to adjust. Anxiety can reduce or even eliminate the potential possessed by inmates, because the anxiety in a prison inmate is that there is a threat to his soul or psyche such as losing the meaning of life (feeling that his future is bleak) and feeling useless. High levels of anxiety can cause disturbances in the future of correctional inmates. This research was conducted with the aim of testing empirically and to determine the effect of self-esteem on anxiety in inmates at the Penitentiary in the Women's Rutan Class II A Medan. The research method used in this study is a quantitative research method. The place of research was carried out at the Class II A Women's Rutan in Medan. In this study the authors distributed questionnaires with a sample of 65 people. From the results of research conducted by the author on the effect of self-esteem on anxiety in inmates at the Women's Rutan Class II A Medan, it shows that the value of the coefficient of determination (R2) is 0.468 or 46.8% indicating the effect of self-esteem on anxiety with a sig. of 0.000 < 0.005.